The Influence of Tourism Attractiveness and Motivation on Visiting Decisions to the Tagepe Noinbila Water Tourism - Lorens Riwu; Asbi Nasar; Lili Agreny Sanam (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
This study aims to analyze the influence of tourism attractiveness and motivation on visiting decisions at the Tagepe Noinbila water tourism site in South Central Timor (TTS). The research employs a quantitative descriptive approach using both primary and secondary data collected through observation, interviews, questionnaires, and literature review. Instrument testing was conducted through validity and reliability assessments to ensure data accuracy. The findings reveal that tourism attractiveness and motivation have a significant effect on visiting decisions, both partially and simultaneously. These results indicate that improving the quality of tourism attractions and strengthening visitor motivation play an important role in encouraging tourists’ decisions to visit the Tagepe Noinbila destination.